2016
DOI: 10.1097/bot.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Exposure Between the Classic and Modified Judet Approaches to the Scapula

Abstract: In conclusion, the MJ approach allows similar access to landmarks important for reduction and fixation while exposing only 20% of the surface area typically visualized with the CJ approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…1,19 In the present study, the percentages of instability and malunion were 0.0% and 0.0%, respectively, for the ring-treated group; and 5.3% and 5.3%, respectively, for the non-ring-treated group during the final follow-up, which were in agreement with previous findings. 1,14,19 Some researchers have highlighted that the rates of instability and malunion were higher after utilizing non-ring fixation than ring fixation. 5,19,21,24 Furthermore, the current study demonstrated higher rates than those published in some previous reports, 25,26 but the rates were lower than those published in the more recent reports.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1,19 In the present study, the percentages of instability and malunion were 0.0% and 0.0%, respectively, for the ring-treated group; and 5.3% and 5.3%, respectively, for the non-ring-treated group during the final follow-up, which were in agreement with previous findings. 1,14,19 Some researchers have highlighted that the rates of instability and malunion were higher after utilizing non-ring fixation than ring fixation. 5,19,21,24 Furthermore, the current study demonstrated higher rates than those published in some previous reports, 25,26 but the rates were lower than those published in the more recent reports.…”
Section: Discussionsupporting
confidence: 93%
“…16,18,19 Generally, a higher clinical complication rate has been detected after non-ring plate fixation than after ring plate fixation. 1,19 In the present study, the percentages of instability and malunion were 0.0% and 0.0%, respectively, for the ring-treated group; and 5.3% and 5.3%, respectively, for the non-ring-treated group during the final follow-up, which were in agreement with previous findings. 1,14,19 Some researchers have highlighted that the rates of instability and malunion were higher after utilizing non-ring fixation than ring fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Harmer et al showed, in a cadaveric study, that the MJ approach exposes only 20 % of the area visualized with CJ but allows similar access to important landmarks for reduction and fixation, minimizing soft-tissue excision [9]. …”
Section: Discussionmentioning
confidence: 99%
“…In 1964, Judet described a posterior approach, which required infraspinatus muscle lateral reflection to expose the infraglenoid fossa and the posterior part of the scapular neck; this approach is known as the classic Judet approach [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation